HUBUNGAN ANTARA KONSUMSI PANGAN DAN AKTIVITAS FISIK DENGAN KADAR KOLESTEROL DARAH PRIA DAN WANITA DEWASA DI BOGOR - Tunggul Waloya; Rimbawan Rimbawan; Nuri Andarwulan (Jurnal Gizi dan Pangan, 2013)
The study was conducted to analyze the association between food consumption and physical activity with blood cholesterol level. The study design was cross sectional located in the District and the Municipality of Bogor. Subjects in this study were 64 adult men and women aged 25—60 years. Stepwise regression test results indicate that the intake of protein, carbohydrate and cholesterol did not significantly affected blood cholesterol levels. Physical activity level and gender significantly affected blood cholesterol levels (p<0.05). Dietary fiber intake and fat intake significantly affected blood cholesterol levels (p<0.10).